HUMAN INTERACTION WITH ARTIFICIAL INTELLIGENCE SYSTEMS UNDER STRESS: TRUST, ERRORS, AND COGNITIVE DECISION-MAKING MECHANISMS - Помиткіна, Любов; Помиткін, Едуард; Кокарєва, Анжеліка (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article highlights the study of psychological mechanisms of human interaction with artificial intelligence (AI) systems under stressful conditions. The aim of the article was to: analyze the psychological mechanisms of human decision-making under stress; identify types of trust errors and algorithmic dependence; and propose a model of cognitive processes that determine the quality of decisions in human-machine systems. Special attention was paid to the phenomena of trust in algorithmic solutions, cognitive biases that are activated during stress, as well as the types of errors that occur in human-machine systems. Modern views on human-AI interaction of leading Ukrainian scientists in psychological science were analyzed. A conceptual model of the interaction “stress – cognitive load – algorithmic influence” is presented, which explains how decision-making changes in the presence of intelligent recommendations. An empirical study based on the author’s questionnaire highlighted the features of interaction with AI in higher education, in particular, its use by students and teachers; it confirmed the thesis that in stressful situations it is difficult to concentrate and make rational decisions. Also important is the conclusion of teachers that the use of AI by students under time pressure leads to an increase in their errors. The conclusions summarize the factors of increasing algorithmic dependence, decreasing situational awareness, and forming trust errors. Practical approaches to designing interfaces and procedures that minimize the risks of incorrect human decisions when using AI in time-limited conditions are substantiated.